Analytical and Mechanical Study of Transtibial Osseo-Integrated Prostheses Implant - Abbas, Saif; Chiad, Jumaa; Takhakh, Ayad; Resan, Kadhim; Fatlawi, Abdullah; Saad, Alaq (Al-Khwarizmi Engineering Journal, 2025)
In amputation surgery, osseointegration is the placement of a metal implant in the residual bone and is conducted with an external prosthesis. In this study, the prospective application of Ti–13Nb–13Zr alloy in a transtibial osseointegrated prosthesis was carefully examined. The alloy demonstrated favourable mechanical properties, such as strong mechanical strength with an average yield strength of 482 MPa, ultimate tensile strength of 551.843 MPa and modulus of elasticity of 74 GPa. In compression testing, the material showed its resilience to compressive loads, exhibiting 700 MPa yield strength and 1010 MPa compressive strength. The elastic modulus of Ti–13Nb–13Zr alloy is approximately 55–65 GPa, which is much closer to that of human bone (10–30 GPa) compared with that of Ti–6Al–4V alloy (110 GPa). This proximity reduces stress shielding, a common issue in implants that a mismatch in stiffness between the implant and bone leads to bone resorption. Analyses using the finite element method demonstrated uniform stress distribution, safety factors and minimal deformation for a range of implant sizes, guaranteeing structural integrity and functionality. The maximal von Mises stress on the tibia bone and implant did not surpass the yield tensile stress of the titanium alloy and bone, which is 470 and 175 MPa, respectively; the maximum safety factor at L=120 and D=3 and the stress levels are not expected to induce material failure. These findings bring up new possibilities for enhanced prosthetic design and use in the field of biomedical engineering by demonstrating the alloy’s potential suitability for osseointegrated prosthetic applications.